Analisis Penerapan Bisnis Model Canvas pada Usaha Mikro Wirausaha Generasi Z - Ericha Tiara Hutamy; Adelia Marham; Andi Naila Quin Azisah Alisyahbana; Nur Arisah; Muhammad Hasan (Penerbit Goodwood, 2021)
Purpose: This study aims to analyze the impact of the canvas model business concept on Generation Z micro-entrepreneurs. Research Methodology: The research methodology used in this study is a descriptive survey to describe and explain how BMC is applied to generation Z micro-entrepreneurs. The data for this study came from informants who are Generation Z online business entrepreneurs. The data collection techniques are questionnaire-based. Results: The research results indicate that the application of the business model canvas to micro-entrepreneurs in Generation Z is 83 percent, which indicates a favorable response from the respondents. Limitations: The study's limitations or weaknesses stem from the research process; the researcher recognizes that a study must contain a deficiency and a great deal of weakness. One of them is in terms of the number of respondents who are only ten people in Generation Z micro-enterprises, which is, of course, insufficient to describe the actual situation. Contribution: The purpose of this research is to develop a business strategy applicable to online micro-businesses by mapping the BMC's nine elements. It is anticipated that this research will increase revenue from product sales and broaden the market for Generation Z micro-entrepreneurs.